Dampak penggunaan gadget terhadap perkembangan sosial emosional dan pemahaman bahasa pada siswa SD IT Insan Permata Malang - Khoiroh, Nabilatul (Maliki Interdisciplinary Journal, 2024)
The use of gadgets has become an integral part of everyday life, including among students of Insan Permata Malang Elementary School (SD IT). However, its impact on the social-emotional development and language comprehension of students needs to be seriously considered. This research employs qualitative research methods to explore the effects of gadget use on SD IT Insan Permata Malang students in terms of social-emotional development and language comprehension. The results show that excessive gadget use tends to reduce social interaction among students, leading to potential emotional isolation. Additionally, gadget use can also disrupt the development of students’ verbal communication skills, which are a key aspect of language comprehension. Meanwhile, there are indications that gadget use may reduce the time allocated for reading and writing, which are crucial aspects of language comprehension. Students tend to be more interested in the digital entertainment offered by gadgets than in reading or writing activities. This impact can affect students’ ability to understand sentence structure and grammar, as well as grasp the meaning of words and phrases in depth.